Blended learning model in Seafarers Training Program for level II technical expert based on the needs of the shipping industry - F. Pambudi Widiatmaka; Tri Joko Raharjo; I Made Sudana; Wirawan Sumbodo; Rizki Setiadi (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2022)
Nowadays, the Level II Technical Expert Seafarers' Training Program learning is conventional. This is burdensome for students due to the increased cost of living for students and needs to be revised. The coronavirus pandemic also limits direct learning. This article discusses the blended learning model for Seafarers Training Program for Level II Technical Experts. This research uses mixed methods. Quantitative methods are used to determine student responses to learning conditions. Student response data was taken using a questionnaire filled in by 41 students. Qualitative methods are used in finding the Blended Learning Model in the Level II Technical Seafarers Training Program Based on the needs of the Shipping Industry. In preparing the data model, the literature review includes blended learning, e-modules, and problem-based learning. The learning model is based on a literature review using the principles of education management. The descriptive analysis describes the model findings of Blended learning at Level II Technical Seafarers' Training. The findings in this article are that The MixPAM (Mixture Blended Problem-based And e-Module) model is a mixture of blended learning and problem-based learning e-module. The results show that the MixPAM model is hypothetically effective and efficient in improving student skills according to industry needs. Professional skills include ship engine repair maintenance (according to industry requirements), ship electrical, control, and ship management systems. Interpersonal skills include communication, teamwork, responsibility, and critical thinking.